Indirect Speech Act Analysis of Indonesian Education Department Students of Serambi Mekkah University - Faisal Faisal; Dinda Saputri; Eli Nurliza; Nurul Azmi; Siti Naila Fauzia; Indani Indani (International Conference on Multidisciplinary Research, 2022)
This study raises the issue about the employment of indirect speech acts of Indonesian language education students at FKIP Serambi Mekkah University. The purpose of this study was to determine the indirect speech acts of Indonesian language education students FKIP Serambi Mekkah University. The research method used is descriptive qualitative method. The data in this study are indirect speech acts of Indonesian language education students, FKIP, Serambi Mekkah University. The subjects in this study were all Indonesian language students. Data collection was carried out by using listening techniques which included tapping techniques, free speaking listening techniques, conversational free listening techniques, recording techniques, and notetaking techniques. The data analysis technique was carried out by means of data reduction, data presentation, interpreting the meaning of the data, and drawing conclusions. The results of the study found that the utterances spoken by Indonesian language education students at FKIP Serambi Mekkah University contained indirect speech acts. In general, the indirect speech acts used by Indonesian students are news sentences which have the intention of commanding the speech partner to do something, then requesting sentences and news sentences that function to ask the speech partner to give something. Speakers use indirect speech acts when interacting so that the speech conveyed seems more polite and not pushy. Keywords : Pragmatics, Indirect Speech Act, Student Speech